Multi-Drugs Resistant Bacteria Associated Particulate Matter In The Ambient Atmosphere of Dhaka, Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2022)
Nowadays, air pollution is confined to the level of air pollutants and bio-aerosols since it might be pathogenic or induce allergic reactions. The research was carried out to discover the bacteria associated with suspended particulate matter in indoor and outdoor air, as well as to investigate their antibiotic susceptibility. The results revealed that the extent of outdoor air pollutants (i.e., PM2.5, PM10, HCHO, and TVOC) was significantly higher (p< 0.01) than the extent of indoor air pollutants. Culturing the sample filter paper in Nutrient Agar (NA) media at two different temperatures, 25°C and 37°C, allowed us to measure the quantity of bacteria in the air. The concentration of bacteria was 622±22 CFUm-3 at 26±2°C and 11±2 CFUm-3 at 20±2°C in both outdoor and indoor air, respectively. Positive Bacillus, Micrococcus luteus, Pseudomonas stutzeri and Brevundimonas diminuta bacteria were identified. All of the identified bacteria were found to be pathogenic. Moreover, some of the identified bacteria showed resistance to some commercially available antibiotics, such as Cefixime, Ceftazimidine, Nalidixic acid, Ampicillin, Ciprofloxacin, Gentamycin, etc. The positive correlation between fine particles and the bacterial concentration (R2= 0.75 for indoor and R2= 0.68 for outdoor air) revealed that the bacteria were highly associated with fine particles than coarse particles. Furthermore, the number and growth of bacteria were affected by the meteorological parameters (i.e., temperature and relative humidity). The rise in relative humidity favoured the increase in bacterial concentration. Therefore, the risk of being affected by bioaerosol is higher in the wet season than that of the dry season.J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(2): 1-12